A comparative study of Cardi‐O‐Fix septal occluder versus Amplatzer septal occluder in percutaneous closure of secundum atrial septal defects. Issue 1 (13th April 2013) - Saritas, Turkay; Kaya, Mehmet Gungor; Yin Lam, Yat; Erdem, Abdullah; Akdeniz, Celal; Demir, Fadli; Erol, Nurdan; Demir, Halil; Celebi, Ahmet
<x xml:space="preserve">Abstract</x> Aim: We sought to investigate the safety and efficacy of Cardio‐O‐Fix septal occluder (CSO) in percutaneous closure of atrial septal defects (ASD) as compared to the Amplatzer septal occluder (ASO). Methods: A consecutive of 351 patients received transcatheter ASD closure with CSO or ASO from July 2004 to October 2010 were studied. The ASDs were divided into simple‐ (isolated defects <26 mm) or complex‐types (isolated defect ≥26 mm, double or multifenestrated defects). The procedures were guided by fluoroscopy and transthoracic or transesophageal echocardiography. Clinical and echocardiographic follow‐ups were arranged before discharge, at 1 month and then every 6‐month after implantation. Results: During the study period, 185 (125 males, aged 18.5 ± 15.6 years) and 166 (103 males, aged 21.0 ± 15.7 years) patients attempted CSO and ASO implants, respectively. The CSO group had similar ASD and device sizes, prevalence of complex lesions (17 vs. 16%, P = 0.796), procedural times and success rates (97% vs. 96%, P = 0.635) as compared to the ASO group. Acute residual shunts were less prevalent in CSO than ASO group and most shunts closed spontaneously at 6‐month follow‐ups. The average equipment cost per patient was lower in CSO group (US$ 4, 100 vs. US$ 5, 900, P < 0.001). The prevalence of device embolization and atrial arrhythmia (all <2%) were similar in both patient groups. Conclusion: Transcatheter ASD occlusion with CSO is safe and effective and it appeared to be an attractive alternative to ASO in closing simple‐type ASD because of its relatively low cost. © 2013 Wiley Periodicals, Inc.